2000
DOI: 10.1016/s0022-2275(20)31973-8
|View full text |Cite
|
Sign up to set email alerts
|

Pristanic acid and phytanic acid: naturally occurring ligands for the nuclear receptor peroxisome proliferator-activated receptor α

Abstract: Phytanic acid and pristanic acid are branchedchain fatty acids, present at micromolar concentrations in the plasma of healthy individuals. Here we show that both phytanic acid and pristanic acid activate the peroxisome proliferator-activated receptor ␣ (PPAR ␣ ) in a concentrationdependent manner. Activation is observed via the ligandbinding domain of PPAR ␣ as well as via a PPAR response element (PPRE). Via the PPRE significant induction is found with both phytanic acid and pristanic acid at concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(45 citation statements)
references
References 35 publications
2
40
1
2
Order By: Relevance
“…Previous reports showed that omega-3 eicosapentaenoic acid (20:5, ω3) and, to a lesser extent, docosahexaenoic acid (22:6, ω3), are potent ligands [96,97] and consistent activators of PPARα [98][99][100], while omega-3 PUFA like linolenic acid (C18:3, ω3) and docosapentaenoic (22:5, ω3) acids, and omega-6 PUFA such as linoleic (C18:2, ω6) and arachidonic (C20:4, ω6) acids are weaker PPARα activators [74,99,100]. In addition, experiments performed by Ellinghaus et al and Zomer et al [101,102] revealed that phytanic acid (3,7,11,15-tertamethylhexadecanoic acid) is a strong natural physiological ligand for PPARα. These assumptions were then followed by reports from Hostetler et al [103], showing that PPARα binds the fatty acyl-CoAs (3-20 nM Kds) and branched-chain fatty acyl-CoA (BCFA-CoAs, phytanoyl-CoA, pristanoyl-CoA; Kds near 11 nM) with the highest affinities (i.e., Kd at nM range).…”
Section: Pparα Natural Ligandsmentioning
confidence: 99%
“…Previous reports showed that omega-3 eicosapentaenoic acid (20:5, ω3) and, to a lesser extent, docosahexaenoic acid (22:6, ω3), are potent ligands [96,97] and consistent activators of PPARα [98][99][100], while omega-3 PUFA like linolenic acid (C18:3, ω3) and docosapentaenoic (22:5, ω3) acids, and omega-6 PUFA such as linoleic (C18:2, ω6) and arachidonic (C20:4, ω6) acids are weaker PPARα activators [74,99,100]. In addition, experiments performed by Ellinghaus et al and Zomer et al [101,102] revealed that phytanic acid (3,7,11,15-tertamethylhexadecanoic acid) is a strong natural physiological ligand for PPARα. These assumptions were then followed by reports from Hostetler et al [103], showing that PPARα binds the fatty acyl-CoAs (3-20 nM Kds) and branched-chain fatty acyl-CoA (BCFA-CoAs, phytanoyl-CoA, pristanoyl-CoA; Kds near 11 nM) with the highest affinities (i.e., Kd at nM range).…”
Section: Pparα Natural Ligandsmentioning
confidence: 99%
“…Obie struktury różnią się istotnie, głównie pod względem innego położenia helisy H12. C. Krótka charakterystyka funkcjonalna dla poszczególnych regionów/ domen RXR; wg [53,54,55,56] najbardziej złożonym fragmentem receptora pod względem funkcjonalnym. Zawiera sekwencję odpowiedzialną za zależną od liganda aktywację transkrypcji (AF2, activation function 2), ponadto jest zaangażowany w niezależną od DNA dimeryzację, oddziaływanie z koregulatorami oraz często w nieobecności liganda pośredniczy w represji transkrypcji [35].…”
Section: Budowa Rxrunclassified
“…w mięsie przeżuwaczy i wyrobach mleczarskich. Kwas fitanowy odpowiada głównie za aktywację homodimerów RXR [83], choć może pełnić również rolę liganda PPAR [56]. Kwas fitanowy aktywuje RXR w stężeniu 10 µM.…”
Section: Ligandyunclassified
“…In addition to hepatocytes with cytosolic catalase, the EM pictures showed cells with increased number of peroxisomes and with enlarged peroxisomes, likely the result of increased PPARα activation. The accumulating phytol breakdown products, phytanic and pristanic acid, can indeed activate PPARα and possibly other transcription factors as well (Kitareewan et al, 1996;Zomer et al, 2000). Enlarged peroxisomes have been described in at least two other mouse models for peroxisomal protein deficiencies, such as the PMP70 (ABCD3) KO mouse (Jimenez-Sanchez et al, 2000) and the phytol fed AMACR KO mouse (Savolainen et al, 2004).…”
Section: )mentioning
confidence: 99%